Actinomicosis cervicofacial: consideraciones importantes sobre una enfermedad imitadora - Mallmann, Lídia (2020)
Actinomycosis is a rare chronic suppurative infection that affects upper airways and the gastrointestinal tract. The aim of this work was to review important information regarding the etiopathogenesis, clinical features and treatment of cervicofacial actinomycosis. According to the anatomic site affected, it is classified into three clinical forms: cervicofacial (50%), thoracic (30%) and abdominal (20%). We present here a literature review focusing on important aspects of cervicofacial actinomycosis. Despite the name comprising the term mycosis, the disease is caused by Gram-positive bacteria of the genus Actinomyces, mainly Actinomyces israelii, which are commensals of the oral microbiota. Nevertheless, when the integrity of the oral mucosa is compromised, they can become pathogenic. Actinomycosis evolves slowly and it often mimics other clinical conditions such as malignancies. Treatment consists in antibiotic therapy and can last up to 12 months in severe cases. Health care professionals’ knowledge about the disease is crucial in a way to promote its prevention, early diagnosis and proper treatment.